Pengaruh E-Service Quality Dan Satisfaction Terhadap Customer Loyalty Pada Marketplace Bukalapak Di Kota Padang - Tia Ardila; Rose Rahmidani (Universitas Negeri Padang, 2023)
This study object to determine the effect of E-Service Quality and Satisfaction on Customer Loyalty at the Bukalapak Marketplace in the city of Padang. This type of research is a causative research. The population in this study is the people of the city of Padang who have used Bukalapak more than 2 times and the determination of the number of samples using the Chocran formula is as many as 97 samples. This research uses side purposive technique. The data used is the type of primary data obtained through the distribution of questionnaires to the people of the city of Padang with predetermined criteria. The analytical method used is path analysis using SPSS 20. The results show that (1) E-Service Quality has a significant effect on Satisfaction (2) E-Service Quality has a significant effect on Customer Loyalty (3) Satisfaction has a significant effect on Customer Loyalty (4) E-Service Quality has a significant effect on Customer Loyalty through Satisfaction.